Emma McChesney and Co. - Ferber, Edna, 1885-1968 (Salt Lake City, UT : Project Gutenberg, 1996)
"Emma McChesney and Co." by Edna Ferber is a novel written during the early 20th century. The story revolves around Emma McChesney, a strong-willed saleswoman who is navigating the competitive world of the women's fashion industry. With a keen business sense and a desire to succeed, Emma is poised to travel to South America to expand her company's reach against the rival Sans-Silk Skirt Company, led by her former colleague, Fat Ed Meyers. At the start of the narrative, we are introduced to Emma McChesney, whose dedication to her son and career sets the stage for her upcoming challenges. The opening chapter depicts her lively dialogue with her business partner, T. A. Buck, highlighting their dynamic partnership. Emma's determination to seize opportunities in South America is met with both skepticism and support from Buck, capturing the tension between their professional ambitions and personal concerns. The initial interactions not only establish Emma's character as a savvy and confident businesswoman but also hint at the unfolding drama between ambition, gender roles, and a budding romance that could complicate their professional lives. (This is an automatically generated summary.)
Broadway to Buenos Aires -- Thanks to Miss Morrissey -- A closer corporation -- Blue serge -- "Hoops, my dear!" -- Sisters under their skin -- An étude for Emma.
Release date is 1996-03-01
Produced by Charles Keller. HTML version by Al Haines.
Keywords: Short stories; McChesney, Emma (Fictitious character) -- Fiction; Traveling sales personnel -- Fiction; Women sales personnel -- Fiction; Businesswomen -- Fiction